Development of mullite fibers and novel zirconia-toughened mullite fibers for high temperature applications - Reinders, Leonie; Pfeifer, Stephanie; Kröner, Sarah; Stolpmann, Heiko; Renfftlen, Achim; Greiler, L. Charlyn; Clauß, Bernd; Buchmeiser, Michael R. (Journal of the European Ceramic Society, 2021)
Polycrystalline mullite fibers and novel zirconia-toughened mullite (ZTM) fibers with average diameters between 9.7 and 10.3 μm containing 3, 7 and 15 wt.-% tetragonal ZrO2 (ZTM3, ZTM7, ZTM15) in the final ceramic were prepared via dry spinning followed by continuous calcination and sintering in air. A shift in the formation of transient alumina phases and tetragonal ZrO2 to higher temperatures with increasing amounts of ZrO2 was observed. Concomitantly, the mullite formation temperature was lowered to 1229 °C for ZTM15 fibers. X-ray diffraction revealed formation of the desired tetragonal crystal structure of ZrO2 directly from the amorphous precursor. Room temperature Weibull strengths of 1320, 1390 and 1740 MPa and Weibull moduli of 9.5, 7.1 and 9.0 were determined for mullite, ZTM3 and ZTM15 fibers, respectively. Average Young’s moduli ranged from 190 to 220 GPa. SEM images revealed crack-free fiber surfaces and compact microstructures independent of the amount of ZrO2.